Characteristics Of Pregnant Women With Premature Rupture Of Membranes In The Hospital. Setio Husodo - Herviza Wulandary Pane; Lili Yuliana Tambunan; Eva Karisma; Rodinih, Rodinih; Ni Nyoman Widya Pradani (Sean Institute, 2024)
Premature rupture of membranes is the rupture of the amniotic membrane before Labor occurs which can occur at gestational age enough time or less time. Premature rupture of membranes is one of the causes of maternal and neonatal infection, preterm labor, hypoxia, fetal defermitas, increased incidence of SC, or failure of Normal delivery. This study aims to determine how the characteristics of pregnant women with premature rupture of membranes based on age, parity, and occupation, in Setio Husodo Kisaran hospital. From the initial survey, the researchers obtained data from the medical records of Setio Husodo Kisaran hospital, found premature rupture of membranes in 99 mothers. This study is descriptive, using secondary data that can be in the medical rocord RS Setio Husodo range“ there is a population of 99 cases and sempel in this study is the entire population of 99.Premature rupture of membranes is often found in pregnant women > 35 years as many as 39 cases (39.4 %), the majority of cases of premature rupture of membranes occur in multiparous pregnant women as many as 22 (22.2 %), cases of premature rupture of membranes in pregnant women who work the majority of IRT 40 ( 40.4 %). Based on the results of the study it can be concluded that premature rupture of membranes is found in many pasa age > 35 years, it is recommended in pregnant women to maintain their health because of age > 35 years where the reproductive organs and other organ functions have begun to decline, so the mother's uterus can not work properly.